Selling Women's History : Packaging Feminism in Twentieth-Century American Popular Culture - Westkaemper, Emily, 1979- (Book collections on Project MUSE., 2017)
"Long before American feminists of the 1960s and the 1970s persuaded universities and the public to treat "women's history" as a valid subject for serious study, popular culture dramatized women's pasts. Sentimentalized visions of eighteenth- and nineteenth-century domestic life saturated the twentieth-century consumer culture landscape. Advertisements lobbied housewives to select "Betsy Ross Red" lipstick, and muffin mix containing "Early American flour." Women's magazines, radio broadcasts, and comic books featured historical biographies of famous and forgotten women, including entrepreneurs, activists, educators, and wives of notable men. Selling Women's History provides the first analysis of these diverse messages about women's histories. As twentieth-century American women assumed new social, political, and economic roles, many historical narratives emphasized continuity, sentimentalizing historical figures like Martha Washington as models for the present. Yet women advertisers, script writers, historians, and consumers responded, constructing more dynamic narratives to promote feminism. This work prefigured the subject matter and analytical approach of academic historians of gender, tracking changes in the expectations for women's behavior over time to demonstrate that society rather than biology had limited women. Advertising women's professional societies, established to expand women's employment opportunities, promoted new facets of such familiar icons as the patriotic Colonial Dame and the Quaker Maid, destabilizing the assertion of feminine domesticity made in advertisements themselves"--